Corneal Abrasion in Hysterectomy and Prostatectomy. (May 2015) - Sampat, Ajay; Parakati, Isaac; Kunnavakkam, Rangesh; Glick, David B.; Lee, Nita K.; Tenney, Meaghan; Eggener, Scott; Roth, Steven
<x xml:space="preserve">Abstract</x> Background: Radical prostatectomy (RP) is most commonly performed laparoscopically with a robot (robotic-assisted laparoscopic radical prostatectomy, R/PROST). Hysterectomy, which may be open hysterectomy (O/HYST) or laparoscopic hysterectomy (L/HYST), has been increasingly frequently done via robot (R/HYST). Small case series suggest increased corneal abrasions (CAs) with less invasive techniques. Methods: The authors identified RP (166, 942), O/HYST (583, 298), or L/HYST (216, 890) discharges with CA in the Nationwide Inpatient Sample (2000–2011). For 2009–2011, they determined odds ratios (ORs) and 95% confidence intervals (CIs) for CA, in R/PROST, non-R/PROST, L/HYST, O/HYST, and R/HYST. Uni- and multivariate models studied CA risk depending on surgical procedure, age, race, year, chronic illness, and malignancy. Results: In 2000–2011, 0.18% RP, 0.13% L/HYST, and 0.03% O/HYST sustained CA. Compared with 17, 554 non-R/PROSTs (34 abrasions, 0.19%) in 2009–2011, OR was not significantly higher in 28, 521 R/PROSTs (99, 0.35%; OR 1.508; CI 0.987 to 2.302; P < 0.057). CA significantly increased in L/HYST (70/51, 323; 0.136%) versus O/HYST (70/191, 199; 0.037%; OR 3.821; CI 2.594 to 5.630; P < 0.0001), further increasing in R/HYST (63/21, 213; 0.297%; OR 6.505; CI 4.323 to 9.788; P < 0.0001). For hysterectomy, risk of CA increased with age (OR 1.020; CI 1.007 to 1.034; P < 0.003) and number of chronic conditions (OR 1.139; CI 1.065 to 1.219; P < 0.0001). CA risk was likewise elevated in R/HYST with number of chronic conditions. Being African American significantly decreased CA risk in R/PROST and in R/HYST or L/HYST. Conclusions: L/HYST increased CA nearly four-fold, and R/HYST approximately 6.5-fold versus O/HYST. Identifiable preoperative factors are associated with either increased risk (age, chronic conditions) or decreased risk (race).